Eldest - Paolini, Christopher (New York : Distributed by Random House, 2005)
After successfully evading an Urgals ambush, Eragon is adopted into the Ingeitum clan and sent to finish his training so he can further help the Varden in their struggle against the Empire.
Map on endpapers.
Booklist.
Publisher's Weekly.
School Library Journal.
Booklist, August 2005.
Christian Library, September 2005.
Keywords: Dragons -- Fiction; Fantasy; Dragons -- Fiction; Fantastic fiction